2014
DOI: 10.2188/jea.je20140018
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologic Features and Prognostic Factors of Coronary Artery Lesions Associated With Kawasaki Disease Based on a 13-Year Cohort of Consecutive Cases Identified by Complete Enumeration Surveys in Wakayama, Japan

Abstract: BackgroundTo clarify the contribution of patient age to the development of coronary artery lesions (CALs) associated with Kawasaki disease (KD), epidemiologic features and prognostic factors were investigated using hospital-based complete enumeration surveys in a specific area.MethodsConsecutive KD cases identified between October 1999 and September 2012 in Wakayama Prefecture, Japan, were analyzed. The primary outcome measure was the presence/absence of CALs (giant aneurysm, mid- or small-sized aneurysm, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
1
6

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 42 publications
0
15
1
6
Order By: Relevance
“…Other previously described risk factors for the development of CAD, like age under 1 year old or older than 9 years old, leukocytosis or hyponatremia were not confirmed in our study, probably because of the sample size limitation. N. Kitano et al, 13 in a cohort of consecutive cases consisting of 1415 patients with KD, found that a rate of patients with CAD was significantly lower in the 11 to 48 month old age group (2%, 17/859), compared to the group of children younger than 11 months old and older than 48 months old (5.2%, 29/556), respectively (p= 0.001). These findings agree with our data because 3 out of the 5 patients with CAD were younger than 11 months old and one was older than 48 months old.…”
Section: Discussionmentioning
confidence: 98%
“…Other previously described risk factors for the development of CAD, like age under 1 year old or older than 9 years old, leukocytosis or hyponatremia were not confirmed in our study, probably because of the sample size limitation. N. Kitano et al, 13 in a cohort of consecutive cases consisting of 1415 patients with KD, found that a rate of patients with CAD was significantly lower in the 11 to 48 month old age group (2%, 17/859), compared to the group of children younger than 11 months old and older than 48 months old (5.2%, 29/556), respectively (p= 0.001). These findings agree with our data because 3 out of the 5 patients with CAD were younger than 11 months old and one was older than 48 months old.…”
Section: Discussionmentioning
confidence: 98%
“…Otros factores de riesgo previamente descritos para el desarrollo de AC, como la edad menor de un año o mayor de 9 años, la leucocitosis o la hiponatremia, no se confirmaron en nuestro estudio, probablemente debido a la limitación que supone el tamaño muestral. N. Kitano et al, 13 en una cohorte de casos consecutivos formada por 1415 pacientes con EK, encontraron que la proporción de pacientes con AC era significativamente menor en el grupo de edad de 11 a 48 meses (2%, 17/859), comparada con el grupo formado por los menores de 11 y los mayores de 48 meses (5,2%, 29/556), respectivamente (p= 0,001). Estos resultados son concordantes con nuestros datos, ya que, de los 5 pacientes con AC, tres eran menores de 11 meses y uno era mayor de 48 meses.…”
Section: 2%unclassified
“…6 KH sistemik bir vaskülit olduğu için temel olarak koroner arterler etkilenmekte ve tedavi edilmeyen olguların %20-25'inde KAH gelişmektedir. 6,7 En sık komplikasyonlardan biri olan koroner arter anevrizmasında, intimal kalınlaşma ve kalsifikasyon sonucunda koroner arter oklüzyonu ve iskemik kalp hastalığı gelişebilmektedir. 7,18 Çalışmamızda da literatürle uyumlu olarak hastaların %25'inde koroner arter tutulumu gözlenmiştir.…”
Section: N (%)unclassified
“…6,7 En sık komplikasyonlardan biri olan koroner arter anevrizmasında, intimal kalınlaşma ve kalsifikasyon sonucunda koroner arter oklüzyonu ve iskemik kalp hastalığı gelişebilmektedir. 7,18 Çalışmamızda da literatürle uyumlu olarak hastaların %25'inde koroner arter tutulumu gözlenmiştir. Akut dönemde verdiğimiz tedaviyle anevrizması olan hastaların yarısında tam iyileşme gözlenirken; kalanında minimal arter dilatasyonu olarak devam etmiştir.…”
Section: N (%)unclassified
See 1 more Smart Citation